Zeolitic Imidazolate Framework (ZIF-8) Decorated Iron Oxide Nanoparticles Loaded Doxorubicin Hydrochloride for Osteosarcoma Treatment - in vitro and in vivo Preclinical Studies - Wu W; Yu X; Sun J; Han Y; Ma Y; Zhang G; Ma Q; Li Q; Xiang H (International Journal of Nanomedicine, 2023)
Wenbo Wu,1,* Xiaoli Yu,2,* Jiaxiang Sun,3 Yuanyuan Han,3 Yuanye Ma,1 Guoqing Zhang,1 Qingming Ma,4 Qiang Li,3 Hongfei Xiang1 1Department of Orthopedics, the Affiliated Hospital of Qingdao University, Qingdao, 266003, People’s Republic of China; 2Department of Anesthesiology, the Affiliated Hospital of Qingdao University, Qingdao, 266100, People’s Republic of China; 3College of Physics, Center for Marine Observation and Communications, Qingdao University, Qingdao, 266021, People’s Republic of China; 4Department of Pharmaceutics, School of Pharmacy, Qingdao University, Qingdao, 266021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongfei Xiang; Qingming Ma, Tel +86-532-61807860, Email xianghf@qdu.edu.cn; qma@qdu.edu.cnBackground: As a broad-spectrum antitumorigenic agent, doxorubicin (DOX) is commonly used as a chemotherapeutic drug for treating osteosarcoma (OS). Still, it is associated with significant cell toxicity and ineffective drug delivery, whereas the zeolite imidazolate framework is extensively applied in the biomedical field as a carrier owing to its favorable biocompatibility, high porosity, and pH-responsiveness. Therefore, we need to develop a drug delivery platform that can effectively increase the antitumorigenic effect of the loaded drug and concurrently minimize drug toxicity.Methods: In this study, a Fe3O4@ZIF-8 nanocomposite carrier was prepared with ZIF-8 as the shell and encapsulated with Fe3O4 by loading DOX to form DOX- Fe3O4@ZIF-8 (DFZ) drug-loaded magnetic nanoparticles. Then, we characterized and analyzed the morphology, particle size, and characteristics of Fe3O4@ZIF-8 and DFZ by TEM, SEM, and Malvern. Moreover, we examined the inhibitory effects of DFZ in vitro and in vivo. Meanwhile, we established a tumor-bearing mouse model, evaluating its tumor-targeting by external magnetic field guidance.Results: DFZ nanoparticles possessed have a size of ~110 nm, with an encapsulation rate of 21% and pH responsiveness. DFZ exerted a superior cytostatic effect and apoptosis rate on K7M2 cells in vitro compared to DOX(p< 0.01). In animal experiments, DFZ offers up to 67% tumor inhibition and has shown a superior ability to induce apoptosis than DOX alone in TUNEL results(p< 0.01). Tumor-targeting experiments have validated that DFZ can be effectively accumulated in the tumor tissue and enhance anticancer performance.Conclusion: In summary, the DFZ nano-delivery system exhibited a more substantial anti-tumorigenic effect as well as superior active tumor targeting of DOX- Fe3O4@ZIF-8 compared to that of DOX alone in terms of biocompatibility, drug loading capacity, pH-responsiveness, tumor-targeting, and anti-tumorigenic effect, indicating its chemotherapeutic application potential.Keywords: osteosarcoma chemotherapy, zeolite imidazolate framework, PH-responsive, nanocarriers, tumor targeting